Financial Feasibility Study of 4-Storey Building Development (Case Study: Center for Language and Culture Building) - Utami, Imanda Prasetya; Putra, I Nyoman Dita Pahang (Jurnal Talenta Sipil, 2025)
Indonesia's rapid population growth, accompanied by significant developments in the field of education, has driven the need for educational facilities. One of the initiatives that can be carried out is the construction of the Center for Language and Culture Building. However, before the construction of the building is carried out, a financial feasibility study should first be carried out. Thus, research was carried out aimed at ensuring that development projects are financially feasible and avoid losses in the future. The method used is the Discounted Cash Flow (DCF) method, using NPV, IRR, BCR, ROI, and Payback Period as the eligibility assessment criteria. The data needed includes building development planning data and building operational data. The results of the analysis are a positive NPV of ID15,312,986,696.52, IRR of 28.28%, BCR of 2.47, ROI of 34.73%, and a payback period of 3 years and 8 months, which shows that the project is feasible to be implemented.